The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/en15093125
|View full text |Cite
|
Sign up to set email alerts
|

Research on Oscillation Suppression Methods in Shunt Active Power Filter System

Abstract: The shunt active power filter (SAPF) system oscillation is a massive threat to the security and stability of the power grid. This study classifies SAPF oscillation into two categories according to the difference in mechanisms. The SAPF oscillation in one category is caused by the resonant characteristics of a switching noise filter and is called external loop amplification. The SAPF oscillation in the other category is induced by the presence of a capacitor in the load current for SAPF and is called self-excit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…It then achieves precise reactive power compensation between layers using the APF, while also suppressing harmonics. This combination of TSC's economy and reliability with APF's accuracy and flexibility has made it widely used in power supply systems [16]. However, in practical applications, it has been observed that under specific operating conditions, harmonic currents at the load side may affect the distribution system, resulting in more severe harmonic resonance phenomena that seriously impact power quality and normal system operation.…”
Section: How Hybrid Compensation Systems Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It then achieves precise reactive power compensation between layers using the APF, while also suppressing harmonics. This combination of TSC's economy and reliability with APF's accuracy and flexibility has made it widely used in power supply systems [16]. However, in practical applications, it has been observed that under specific operating conditions, harmonic currents at the load side may affect the distribution system, resulting in more severe harmonic resonance phenomena that seriously impact power quality and normal system operation.…”
Section: How Hybrid Compensation Systems Workmentioning
confidence: 99%
“…The TSC enables graded reactive power compensation [13], while the APF compensates for harmonics and provides stepless continuous compensation of reactive power between TSC stages [14]. This system achieves simultaneous reactive power compensation and harmonic current suppression, resulting in excellent compensation effects and better economy [15,16]. As a result, this hybrid system has been widely adopted.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing number of non-linear powerful consumers asymmetrically connected to the power supply system leads to a deterioration in the power quality and increasing power losses. The most effective hardware for improving power quality in points of common coupling is shunt active filters (SAFs), which improve the harmonic content of the consumed currents and compensate for inactive power components, minimizing power losses in the transmission line [1][2][3]. These works also aim to assess the most advanced SAFs by reducing the number of power switches and focusing on reducing grid-connected inverters' cost, size, and weight.…”
Section: Introductionmentioning
confidence: 99%